PUNICA GRANATUM L-ANORNING KIMYOVIY VA DORIVOR HUSUSIYATLARI TAHLILI (Proceedings of International Educators Conference, 2022)
The chemical composition of pomegranate is distinguished by its healing properties. Different parts of pomegranate fruit contain metabolites and various sugars, organic acids, polyphenols, flavonoids, anthocyanins, fatty acids, alkaloids, vitamins and others. Pomegranate extract has anticarcinogenic activity against many cancers. Another ingredient that plays a major role in pomegranate as a functional food is anthocyanins. From this study, pomegranate fruit, juice extract and other products were analyzed based on beneficial and functional in vitro and in vivo studies.